Anti-hyperlipidemic Activity of Carissa carandas (Auct.) Leaves Extract in Egg Yolk Induced Hyperlipidemic Rats - Sumbul, S.; Ahmed, S. I. (Journal of Basic & Applied Sciences, 2012)
The Purpose of this study was to examine the lipid lowering activity of aqueous: ethanol (1:1) extract of Carissa carandas in Egg yolk induced hyperlipidemic rats. A highly significant increase in the weight of group C (High cholesterol diet) rats was observed when compared with control group N (P<0.01). The extract caused a significant reduction in body weight, Cholesterol, Triglycerides, HDL and LDL in hyperlipidemic rats. Histopathological changes induced by high cholesterol diet were also significantly reduced by the extract. The activity of ethanol and water extract of C. carandas was comparable to that of atorvastatin.